Liquid crystal spiral phase plate : design, fabrication and characterization - Wang, Qin (2010)
Optical vortices have both theoretical and application value, and have attracted many research interests. Using spiral phase plates (SPP) to generate optical vortices has the advantages of high conversion efficiency and flexibility in applications. Moreover, SPP have found applications in edge contrast enhancement in microscopy, optical vortex coronagraph and generating radially polarized beams etc. Among various kinds of SPP, Liquid crystal spiral phase plates (LC SPP) have the potential advantages of dynamic switching between optical vortices with different topological charge, adaptability to any visible wavelength and capability to realize high slice number etc. These are unique advantages of LC SPPs comparing with other kinds of SPP.